DEVELOPING EARLY WRITING READINESS THROUGH TEACHERS’ EFFORTS AND CHILDREN’S ENGAGEMENT IN ISLAMIC KINDERGARTEN - Al Baqi, Safiruddin; Rosyidah, Afidatur; Fatmawati, Dwi; Muthi'ah; Nurin Nur Aini; Septiana; Nurasyia S. Usman (ALAYYA : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to describe the efforts of teachers and children's involvement in developing writing readiness in early childhood at Siti Khadijah Islamic Kindergarten Ponorogo. Writing readiness is understood as a part of early literacy that includes fine motor skills, symbol recognition, and motivation to write. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. Data analysis was carried out with the Miles and Huberman interactive model, which included reduction, presentation, and conclusion drawn. The results of the study showed that teachers played the role of facilitators who provided gradual guidance, individual support, and positive reinforcement in writing learning. Children show varied involvement, influenced by motivation, confidence, and the emotional atmosphere of the class. The integration of Islamic values such as patience, discipline, and gratitude strengthens the learning process and shapes children's character. This study concludes that children's writing readiness develops through the synergy between teacher strategies, child involvement, and spiritual values embedded in Islamic education. The implications of these findings emphasize the importance of learning to write that is fun, adaptive, and based on Islamic values in the development of early childhood literacy.